Revisiting Indolo[3, 2‐b]carbazole: Synthesis, Structures, Properties, and Applications. (1st April 2020) - Zhao, Mengna; Zhang, Binghao; Miao, Qian
Abstract: Indolo[3, 2‐ b ]carbazole presents a π‐skeleton with a remarkable electronic structure and interesting potential applications. It is, however, also associated with ambiguity and controversy. Herein, new derivatives of indolo[3, 2‐ b ]carbazole are reported and they have enabled a comprehensive study on the electronic structure of indolo[3, 2‐ b ]carbazole and the development of a new n‐type organic semiconductor. Experimental and computational studies show that indolo[3, 2‐ b ]carbazole has a largely localized p ‐benzoquinonediimine moiety and significant antiaromaticity. When substituted with (4‐silylethynyl)phenyl groups, the indolo[3, 2‐ b ]carbazole exhibits one‐dimensional π–π stacking and functions as an n‐type organic semiconductor in solution‐processed field effect transistors. Abstract : The syntheses of new derivatives of indolo[3, 2‐ b ]carbazole have enabled a comprehensive study on the remarkable electronic structure of indolo[3, 2‐ b ]carbazole. This work has also led to the development of a new n‐type organic semiconductor for solution‐processed organic field effect transistors.